THE DIFFERENCE OF EFFECTIVITY BETWEEN MANGOSTEEN PEEL EXTRACT AND METRONIDAZOLE ON FIBROBLAST PROLIFERATION - Atiqah, Adinda Nur; Poetri, Adisty Restu; Niam, Moh Husnun (Odonto : Dental Journal, 2021)
Background: The disease of the oral cavity is quite common in the society is periodontitis. The main cause of this condition is a certain bacterial infection found in dental plaque. In general, metronidazole gel will be given as additional therapy to treat bacterial colonization. Mangosteen peel extract gel contains xanthones and flavonoids which are known to be antibacterial and anti-inflammatory. This research aims to specify the differences in the effectiveness of anti-inflammatory between mangosteen peel extract and metronidazole gel on fibroblast proliferation.Method: This is a laboratory experimental design using post-test only design consisted of 50% mangosteen peel extract gel group, 75% mangosteen peel extract gel group, 25% metronidazole gel group and metronidazole plus gel group. This research used male Wistar rats induced periodontitis by ligation for 7 days as samples.Results: The results reveal that there was a differences in effectiveness between the 4 groups against the proliferation of fibroblast were analyzed using One Way ANOVA with a significance of 0.000 (p<0.05).Conclusion: It can be concluded that there was differences in the effectiveness of mangosteen peel extract gel and metronidazole gel as anti-inflammatory on proliferation of fibroblast in periodontitis healing process.